2020
DOI: 10.1080/22797254.2020.1801355
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Forecasting reference evapotranspiration using data mining and limited climatic data

Abstract: To accurate forecast of water evaporation and transpiration (reference evapotranspiration, ET 0) is imperative in the planning and management of water resources. The Penman-Monteith FAO56 (PM-56) equation which is recommended for estimating ET 0 across the world. However, it requires several climatic variables; the use of the PM-56 equation is restricted by the unavailability of input climatic variables in many locations. In the current study, the potential of k-Nearest Neighbor algorithm (KNN), which is a dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The next article is entitled "Forecasting Reference Evapotranspiration Using Data Mining and Limited Climatic Data," and it is co-authored by Feng and Tian (2020). The authors make a more detailed research on seismic forward modeling of hydrothermal dolomite.…”
Section: Guest Editorial Of the Special Issue "Remote Sensing In Water Management And Hydrology"mentioning
confidence: 99%
“…The next article is entitled "Forecasting Reference Evapotranspiration Using Data Mining and Limited Climatic Data," and it is co-authored by Feng and Tian (2020). The authors make a more detailed research on seismic forward modeling of hydrothermal dolomite.…”
Section: Guest Editorial Of the Special Issue "Remote Sensing In Water Management And Hydrology"mentioning
confidence: 99%
“…Numerous studies in the agriculture domain (Del Grosso et al 2008;Sun and Du 2017;) have focused on estimating crop-productivity variables (i.e., AET, RET, and NPP) from meteorological factors, and finding associations between them. However, there have been a few attempts at using traditional models (such as KNN (Feng and Tian 2021) and ARIMA (Landeras, Ortiz-Barredo, and López 2009)) and neural models (Alves, Rolim, and Aparecido 2017) to predict ET. These studies found that statistical/ML models are more accurate than Historical Average methods (which do not involve learning).…”
Section: Related Workmentioning
confidence: 99%
“…k-Nearest Nearest-Neighbor Algorithm Potentials, an ET0 estimation data mining tool, have been explored in semi-arid China, using minimal climate data [16]. Furthermore, the PM-56 equation was checked with a KNN-dependent ET0 prediction model.…”
Section: Related Workmentioning
confidence: 99%